2018
DOI: 10.1016/j.celrep.2018.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Microcephaly Modeling of Kinetochore Mutation Reveals a Brain-Specific Phenotype

Abstract: SUMMARY Most genes mutated in microcephaly patients are expressed ubiquitously, and yet the brain is the only major organ compromised in most patients. Why the phenotype remains brain specific is poorly understood. In this study, we used in vitro differentiation of human embryonic stem cells to monitor the effect of a point mutation in kinetochore null protein 1 ( KNL1;CASC5 ), identified in microcephaly patients, during in vitro b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…This raises the question as to why mutations that mostly disrupt the coding-sequences of genes temporally dynamic in multiple organs lead to diseases that are organ-specific. A number of different factors may explain this phenomenon, including alternative splicing (e.g., mutations may affect only organ-specific isoforms) [26], functional redundancy [25], and/or dependency on the characteristics of specific cell types (e.g., protein-misfolding diseases in long-lived neurons). It has also been suggested that pathologies tend to be associated with the organ where the genes display elevated expression [24].…”
Section: Resultsmentioning
confidence: 99%
“…This raises the question as to why mutations that mostly disrupt the coding-sequences of genes temporally dynamic in multiple organs lead to diseases that are organ-specific. A number of different factors may explain this phenomenon, including alternative splicing (e.g., mutations may affect only organ-specific isoforms) [26], functional redundancy [25], and/or dependency on the characteristics of specific cell types (e.g., protein-misfolding diseases in long-lived neurons). It has also been suggested that pathologies tend to be associated with the organ where the genes display elevated expression [24].…”
Section: Resultsmentioning
confidence: 99%
“…Mutant neural progenitors underwent a lengthening of mitosis that was associated with cytokinesis failure, cell death, and premature differentiation toward astrocytes and neurons. Finally, using 3D neural spheroids, the authors showed a reduction in the size of mutant spheroids, which could be attributed to reduced proliferation and premature differentiation of the neural progenitors [102]. Although differences in KNL1 protein levels had not been reported in patients fibroblasts or lymphocytes in previous work [51], decreased levels of KNL1 were found to be present in mutant neural progenitors, possibly reflecting neural-specific differences in KNL1 mRNA processing.…”
Section: Casc5/knlmentioning
confidence: 83%
“…Although differences in KNL1 protein levels had not been reported in patients fibroblasts or lymphocytes in previous work [51], decreased levels of KNL1 were found to be present in mutant neural progenitors, possibly reflecting neural-specific differences in KNL1 mRNA processing. In contrast, mutant fibroblasts and mutant neural crest cells showed no reduction in KNL1 levels and no defective growth, demonstrating that the KNL1 mutation affects only neural progenitors, which was possibly due to the higher levels of splicing proteins that were identified in these cells [102].…”
Section: Casc5/knlmentioning
confidence: 92%
See 1 more Smart Citation
“…Another possibility may lie in alternative splicing. The brain undergoes the most alternative splicing events than any other tissue and expresses the largest number of splicing factor genes (170). This means that the brain produces more diverse protein isoforms than other tissue types.…”
Section: Remaining Questionsmentioning
confidence: 99%